Lipin1 deficiency causes sarcoplasmic reticulum stress and chaperone‐responsive myopathy. (12th November 2018) - Rashid, Talha; Nemazanyy, Ivan; Paolini, Cecilia; Tatsuta, Takashi; Crespin, Paul; de Villeneuve, Delphine; Brodesser, Susanne; Benit, Paule; Rustin, Pierre; Baraibar, Martin A; Agbulut, Onnik; Olivier, Anne; et al.
Abstract: As a consequence of impaired glucose or fatty acid metabolism, bioenergetic stress in skeletal muscles may trigger myopathy and rhabdomyolysis. Genetic mutations causing loss of function of the LPIN1 gene frequently lead to severe rhabdomyolysis bouts in children, though the metabolic alterations and possible therapeutic interventions remain elusive. Here, we show that lipin1 deficiency in mouse skeletal muscles is sufficient to trigger myopathy. Strikingly, muscle fibers display strong accumulation of both neutral and phospholipids. The metabolic lipid imbalance can be traced to an altered fatty acid synthesis and fatty acid oxidation, accompanied by a defect in acyl chain elongation and desaturation. As an underlying cause, we reveal a severe sarcoplasmic reticulum (SR) stress, leading to the activation of the lipogenic SREBP1c/SREBP2 factors, the accumulation of the Fgf21 cytokine, and alterations of SR–mitochondria morphology. Importantly, pharmacological treatments with the chaperone TUDCA and the fatty acid oxidation activator bezafibrate improve muscle histology and strength of lipin1 mutants. Our data reveal that SR stress and alterations in SR–mitochondria contacts are contributing factors and potential intervention targets of the myopathy associated with lipin1 deficiency. Synopsis: Loss‐of‐function mutations of ER‐resident phosphatidate phosphatase lipin1 ( LPIN1 ) frequently lead to severe muscle injury in children, but the underlying cellular mechanism remains elusive. Here, genetic analysis identified sarcoplasmic reticulum (SR) stress response and altered mitochondrial morphology as primary causes for detrimental lipid accumulation, pointing to potential therapeutic interventions. Skeletal muscle specific Lpin1 depletion in mice results in myopathy. Lipin1 mutant muscles show increased fatty acid biosynthesis and lipid levels. Lipin1 deficiency triggers unfolded stress response and SR fragmentation. mtDNA levels and SR‐mitochondria contacts are impaired at Lpin1 deletion. Lipin1‐dependent myopathy is rescued by treatment with the chaperone TUDCA or fatty acid oxidation agonist bezafibrate. Abstract : ER stress response and altered mitochondrial functions are central to metabolic muscle injury upon loss of lipin1.